Performance of a Triple Cantilever Hybrid Energy Harvester (TCHEH) Based on the Triboelectric Surface Modification - Azwan M.K.; Salleh H.; Rao S. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The aim of this study is to characterise the performance of a Triple Cantilever Hybrid Energy Harvester (TCHEH) based on the triboelectric surface modification. The application is to harvest sufficient amount of power for low power sensor node. The whole system comprises of three separated generators being put together into one prototype with the design of triple cantilever beam. The triple cantilever consists of top and bottom triboelectric energy harvester (TEH) and middle section piezoelectric energy harvester (PEH). The top and bottom section is the Polytetrafluoroethylene (PTFE). The testing for TEH consists of pairing the highest negative charged material which is Polytetrafluoroethylene (PTFE) with few other positively charged materials. The best pair was used for further testing by modifying the triboelectricsurface in order to increase the power output. At the frequency of 13Hz and acceleration at 0.27gms-2, the ideal opened-circuit voltage, VOC produced for top THE was 2.23V and for the bottom THE was 2.24V, while for the PEH was 9.27V. The final prototype of TCHEH produced an optimum power of 7.29mW at a resistance of 9k?. The power density obtained from the prototype was7.36Wm-2 which enable the low power sensor node to power up. BEIESP.